ASSESSMENT OF MORTALITY IN LIVER CIRRHOSIS AND ACUTE KIDNEY INJURY CASES - MUKHTAR, S; SHAHID, ZB; HUSSAIN, I; ULLAH, N; ATHER, MM; RASHEEQ, T (Biological and Clinical Sciences Research Journal, 2023)
The current analysis was designed to assess the short-term mortality in liver cirrhosis patients with acute kidney disease and assess the predictive factors of such mortality. A prospective study was conducted in the Department of Medicine & Gastroenterology of Bakhtawar Amin Hospital Multan from January 2022- January 2023. A total of 100 decompensated cirrhotic patients with acute kidney injury were included in the study. Baseline serum creatinine levels were measured at admission and every day after admission in all patients. Prothrombin time, ascitic fluid examination, and basic liver and kidney function tests were performed on every patient after admission. The patients' complications, death during the hospital stay, and 30-day mortality were noted for all admitted patients. Among 100 patients, 90 (90%) were male, and the mean age was 47. The cause of liver failure in 51% of patients was the Hepatitis B virus, and 93% of patients presented with ascites. The type of acute kidney injury and its stage, CTP and MELD score, HE, serum bilirubin and creatinine, PT, jaundice, and SGOT were mortality predictors. The MELD score showed an accuracy of 77.5%, and the CTP score had a 73.44% accuracy in predicting short-term mortality. Based on the results, the type of acute kidney injury and its stage, CTP and MELD score, HE, serum bilirubin and creatinine, PT, jaundice, and SGOT are mortality predictors in cirrhotic patients with acute kidney injury